براہوئی املا، نوشت نا وئیل آک: Brahui Language; Orthographical and Lettering Problems - Farooq, Ummar (Al-Burz, 2012)
This research article shows the orthographical and lettering problems in Brahui writing. There is no any own script for Brahui despite of 700 years’ literary history this language. It furthers discuss the alphabetical issues, the vowels, consonants and diphthongs. This article rejects the Dr.Brahui reference about brahui script that the "Mahara sa raja ta raja sa" it is baseless discussion that Brahui writing style has found in Kajola Kad fezas period. Brahui has been written in Arabic, Latin, Sindhi and Persian script from 1292 to up to date. These borrowing scripts created complexity in Brahui writing manner.